A systems theory perspective on the relationship between practice and research in the making disciplines - Riis, Kirstine (FormAkademisk, 2013)
This article discusses the relationship between practice and research in the making disciplines. The discussion is based on a systems theory with reference to the German sociologist Niklas Luhmann (2007) and the way Rasmussen, Kruse and Holm (2007) use Luhmann´s theory. This article constructs and emphasizes the fundamental difference between the practice system and the scientific system. Furthermore, it highlights the distinctions between practice as the development of knowledge and research as the generation of knowledge. In addition to these boundaries, the following four different forms of knowledge are classified and described:1) practical knowledge and 2) professional knowledge, which are both associated with the practice system, and 3) research knowledge and 4) philosophy of science knowledge, which are associated with the scientific system. While emphasizing a fundamental difference between the practice system and the scientific system, this article assumes that art and design research should deal with aspects from both systems. The systems theory term ‘structural coupling’ offers a way to enable the two systems to influence each other while maintaining their own boundaries. Insider research is a structural coupling between the practice system and the scientific system. By exploring art and design processes from within as both the practitioner and the researcher, it is possible to generate knowledge both about and for practice. This article considers art and design research as a subsystem of the scientific system and argues that this approach may strengthen the further development of art and design research.